Clinical features, exercise hemodynamics, and determinants of left ventricular elevated filling pressure in heart‐transplanted patients. (5th October 2015) - Clemmensen, Tor Skibsted; Eiskjær, Hans; Løgstrup, Brian Bridal; Mellemkjær, Søren; Andersen, Mads Jønsson; Tolbod, Lars Poulsen; Harms, Hendrik J.; Poulsen, Steen Hvitfeldt
Summary: This study aimed to assess clinical, functional, and hemodynamic characteristics of heart‐transplanted (HTX) patients during exercise. We performed comprehensive echocardiographic graft function assessment during invasive hemodynamic semi‐supine exercise test in 57 HTX patients. According to hemodynamics findings, patients were divided into Group A: normal left ventricular (LV) filling pressure (FP): pulmonary capillary wedge pressure (PCWP) <15 mmHg at rest and <25 mmHg at peak exercise, and Group B: elevated LV‐FP: PCWP ≥15 mmHg at rest or ≥25 mmHg at peak exercise. Thirty‐one patients (54%) had normal LV‐FP and 26 patients (46%) had elevated LV‐FP. The latter had higher cumulative rejection burden ( P < 0.01) and were more symptomatic (NYHA class >1) ( P < 0.05), and cardiac allograft vasculopathy (CAV) was more prevalent ( P < 0.05). With exercise, the changes in both left‐ and right‐sided filling pressures were significantly increased, whereas LV longitudinal myocardial deformation was lower ( P < 0.05) in patients with elevated LV‐FP than in patients with normal LV‐FP. No between‐group difference was observed for cardiac index or LV ejection fraction (LVEF) during exercise. In conclusion, elevated LV‐FP can be demonstrated in approximately 50% of HTX patients. Patients with elevated LV‐FP have impaired myocardial deformation capacity, higher prevalence of CAV, and higher rejection burden, and were more symptomatic. Exercise test with the assessment of longitudinal myocardial deformation should be considered in routine surveillance of HTX patients as a marker of restrictive filling (ClinicalTrials.gov Identifier: NCT02077764).